Asuhan Kebidanan Nifas & Menyusui : Teori dalam praktik kebidanan Profesional - Andina Vita Sutanto (Pustaka Baru Press, 2018)
membahas Nifas & Menyusui dalam Teori dalam praktik kebidanan Profesional